Ensaio sobre o discurso amoroso - Vasconcellos, Victor Hugo da Silva (2015)
This research deals with the amorous discourse and its constitution. The theme of love is discussed aiming to analyze the manifestations that appear under its name. Love is a subject approached by different areas of knowledge, what doesn t strain its study. In this study, I focus on the love of a straight couple in the twentieth-one century and the discursive manifestations willing the amorous accomplishment. The research objective is the constitution of amorous discourse as an autonomous discourse. My investigation will be driven by the recognition of linguistic mechanisms that structure the amorous discourse; also, using the inter-discourse postulation, to analyze the mechanisms of discourse to recognize the discursive field of love; to reflect if there is different characteristics in this discourse when compared with political discourses, e.g. I start from the hypothesis that the amorous discourse is an atopic discourse belonging to discursive field of love. The atopia of this discourse is characterized by the restricted manifestation of the speakers, so I tend to justify this hypothesis though the reflection about atopia and the discursive peculiarities. Another hypothesis to analyze this discourse is the ethos and the split in ethosessence, alter-ethos and alter-essence. That made, I will verify if there are unfolding in the discourse under analysis and to confirm if this ethical manifestations occur and the effects provoked though discourse. The methodology used is the interpretation of the selected amorous discourses and the application of analysis categories: discursive field, inter-discourse and ethos. The theoretical foundation used is french discourse analysis, mainly, supported by Dominique Maingueneau works. The results of this research pointed that the amorous discourse can be considered a discourse and that love discursive field is based upon a historical and social archive. The research also showed that is possible the unfolding of ethos and its manifestations in the amorous discourse. The social issue of love was approached through seduction. The love in its discourse appeared to be strong, firm; but also fragile and manipulator